Análisis del marco legal para la implementación y desarrollo del proceso de paz con los grupos paramilitares (2016)
During the first decade of the 21st century, Colombia began a peace process, which was passed by Congress in 2005, called “Justice and Peace Law”. This law was aimed at armed groups outside the law known as Paramilitaries. This process was highly relevant to the social, political and economic life of the country. The “Justice and Peace Law” which led to disarmament and the integration into civilian life of more than 30,000 former combatants. With this study, we intend to make a legal analysis of the base and fulfill the objectives of the legal process, the obstacles they have faced, reforms as well as criticism than it has faced. We also want to highlight the importance of Transitional Justice in a peace process, which exposes its main objectives.